잘피, 거머리말 종자의 건조에 따른 발아율과 함수율 - 박정임; 김종협; 김종렬; PARK, JUNG-IM; KIM, JONG-HYEOB; KIM, JONG-RYOL (Pada (Hanʼguk Haeyang Hakhoe), 2017)
Eelgrass, Zostera marina is a marine flowering plant that grows in submerged habitats for most of its lifetime, and experiences desiccation stress when exposed to air. Although the desiccation stress observed in adult eelgrass has been frequently studied, there has been little research on desiccation stress in eelgrass seeds. To survey desiccation stress in eelgrass seeds, we studied the germination rate and moisture content upon desiccation caused by exposure to air. The germination rate of the eelgrass seeds exposed to air for 1 hour at $20^{°}C$ and 50% relative humidity decreased markedly, and it decreased consistently as the exposure time increased. Eelgrass seeds exposed to air for longer than 11 hours did not germinate. As the exposure time of eelgrass seeds to air increased, the germination rate and moisture content decreased, showing a negative correlation. In addition, eelgrass seeds exposed to air at $30^{°}C$ showed significantly lower germination rates than those exposed to air at $10^{°}C$ or $20^{°}C$. Our results revealed that desiccation causes a decrease in the germination of eelgrass seeds, which will provide useful information for eelgrass habitat restoration using seeds. 거머리말은 해양 현화 식물로 일생의 대부분을 해수 내에서 생활하며, 공기에 노출시 건조 스트레스를 받게 된다. 지금까지 거머리말 성체에서 나타나는 건조 스트레스는 다수 알려진데 비해, 거머리말 종자의 건조 스트레스에 대한 정보는 부족한 편이다. 이 연구는 거머리말 종자의 건조 스트레스를 알아보기 위해 공기 중 노출로 인한 종자의 발아율과 함수율의 변화를 실험하였다. 상대습도 50%, $20^{°}C$의 공기에 1시간 노출된 거머리말 종자의 발아율은 현저히 감소되었으며, 노출시간이 길어질수록 종자의 발아율은 지속적으로 감소하였고, 11시간 이상 노출된 종자는 전혀 발아하지 않았다. 거머리말 종자의 공기 노출시간이 길어질수록 발아율과 함수율은 감소하는 음의 상관관계가 나타났다. 또한, $30^{°}C$의 공기에 노출된 거머리말 종자는 $10^{°}C$와 $20^{°}C$의 공기에 노출된 거머리말 종자보다 현저히 낮은 발아율을 나타내었다. 따라서 거머리말 성체가 공기 중 노출 시 건조 스트레스를 겪는 것처럼 거머리말 종자도 건조에 의한 발아율의 감소가 확인되었으며, 이것은 종자를 활용한 거머리말 서식지 복원 사업에 유용한 정보를 제공하고자 한다.